Experimental investigation on wear behaviors of TBM disc cutter ring with different cooling methods. (April 2022) - Fu, Jie; Zeng, Guiying; Zhang, Hao; Zhang, Ling; Yin, Xuanwei; Xia, Yimin
Highlights: The TBM cutter ring and rock wear experiment with different cooling methods were carried out. The influence of different cooling methods on the wear loss weight, the working temperature, and the surface appearance were analyzed. The reasons for the change in the wear mechanism of the cutter ring were analyzed by conducting high-temperature hardness tests. Abstract: The cutter ring of the TBM disc cutter is the main tool that directly contacts and cuts the rock. The cutter ring is prone to wear during the tunneling process, and the lower wear life will drastically reduce the tunneling efficiency and increase the construction cost. The working temperature of the cutter ring is an important factor affecting its wear resistance. TBM cutter cooling measures do not produce satisfactory results when tunneling in hard rock environments. When the cooling is not timely, the working temperature of the disc cutter ring will reach more than 400℃. Therefore, this paper carried out the cutter ring and rock wear experiment with water and air as the cooling medium. After analyzing the influence of different cooling methods on the weight loss, the working temperature and the wear mechanism, the result is obtained as follows: (1) The working temperature under water mist cooling is the lowest, and its wear loss is reduced by 65.2% compared with the non-cooling state. Under 30 m/s air flow rate cooling condition, the weight loss dropped by 22.5%. (2) The hardness of the cutter ring material will gradually decrease as the temperature rises. As the working temperature increases, the ploughing wear mechanism with plastic characteristics will appear. (3) The lubrication of water and the drop in the vertical force load after the rock absorbs water are also important factors to reduce the wear of the cutter ring.